An Integrated Financial Management Information System and the Quality of Financial Reports Among Government Institutions in Kenya - Tum, Patrick Cheruiyot; Ondabu, Ibrahim Tirimba (International Journal of Finance Research, 2023)
The use of Integrated Financial Management Information System among the Government institutions in Kenya is crucial in improving the management of accounting and financial reporting data so as to enhance efficiency and effectiveness in government institutions financial reporting processes. This research study was set to establish the effect of integrated financial management information system on quality financial reporting. The research targets a population of 68 government institutions (47 county government and 21 ministries) in Kenya who were purposively selected as the Integrated Financial Management Information System users and also forming the unit of analysis for the study. The primary data was collected through the use of questionnaires and then the data was analyzed using multiple regression model and descriptive statistics where the study made use of STATA software version 12 application to examine the relationship of the predictor and response variables. The study established that electronic budgeting and automated cash management positively and significantly influence the quality of financial reporting among the government institutions in Kenya. The study further establishes that electronic procurement and automated financial reporting positively and insignificantly influences the quality of financial reporting among the government institutions in Kenya.